Retinal flow cytometer - Alt, Clemens; Veilleux, Israel; Pitsillides, Costas (My University, 2007)
The in vivo flow cytometer is an instrument capable of continuous, real-time monitoring of fluorescently labeled cells in the circulation without the need to draw blood samples. However, the original system probes a single vessel in the mouse ear; the small sample volume limits the sensitivity of the technique. We describe an in vivo retinal flow cytometer that simultaneously probes five artery–vein pairs in the mouse eye by circularly scanning a small laser spot rapidly around the optic nerve head. We demonstrate that the retinal flow cytometer detects about five times more cells per minute than the original in vivo flow cytometer does in the ear
Keywords: Flow cytometry; Optical instruments; Cells; Real-time control; Mice; Lymphocytes